Surface energetics of poly(N-vinyl-2-pyrrolidone)/chitosan blend films - EROĞLU, MEHMET SAYIP (ELSEVIER SCIENCE BV, 2006)
Poly(N-vinyl-2-pyrrolidone) (PVP) and chitosan (CTS) with three different molecular weights (MW: 150,000, 400,000 and 600,000 g/mol) blends were prepared as films having 13, 20, 33, 43 and 50 % (w/w) CTS by solution casting method. Surface properties of the films were analyzed by contact-angle measurements and scanning electron microscopy (SEM). The contact angles of water, glycerol, ethylene glycol, formamide and paraffin oil drop were measured on these films. The contact-angle results were evaluated in terms of surface free energy components by using Van Oss-Good methodology. It was found that all PVP/CTS blend surfaces are enriched in low surface free energy component, i.e. CTS. This conclusion was further confirmed by the cross-sectional SEM images observation of these blends. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: surface energy; contact angle; blends; chitosan; BIOARTIFICIAL POLYMERIC MATERIALS; SWELLING PROPERTIES; HYDROGELS; CHITOSAN; SYSTEMS; IPN